Holocene rate of slip and tentative recurrence interval for large earthquakes on the San Andreas fault, Cajon Pass, southern California - Sieh, Kerry (2013)
Detailed mapping of the San Andreas fault zone, where it crosses Cajon Creek in Southern California, has revealed a number of late Quaternary deposits and geomorphological features offset by the fault. Radiocarbon dating of these alluvial and swamp deposits has provided a detailed chronology with which to characterize the activity of the San Andreas fault.